2004
DOI: 10.4049/jimmunol.173.3.2078
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Expressed Chemokine/CC Chemokine Ligand 16 Attracts Eosinophils by Interacting with Histamine H4 Receptor

Abstract: Liver-expressed chemokine (LEC)/CCL16 is a human CC chemokine that is constitutively expressed by the liver parenchymal cells and present in the normal plasma at high concentrations. Previous studies have shown that CCL16 is a low-affinity ligand for CCR1, CCR2, CCR5, and CCR8 and attracts monocytes and T cells. Recently, a novel histamine receptor termed type 4 (H4) has been identified and shown to be selectively expressed by eosinophils and mast cells. In this study, we demonstrated that CCL16 induced pertus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
1
44
0
2
Order By: Relevance
“…H4R-induced chemotaxis or cytoskeletal changes have been described recently in other cell types such as eosinophils (43)(44)(45) and mast cells (38). A recent study also showed that the CC chemokine CCL-16 mediates chemotaxis via the H4R in eosinophils (46). Thus, histamine might play a role in the accumulation of DC and other cell types in allergic diseases such as atopic dermatitis or contact dermatitis.…”
Section: Discussionmentioning
confidence: 98%
“…H4R-induced chemotaxis or cytoskeletal changes have been described recently in other cell types such as eosinophils (43)(44)(45) and mast cells (38). A recent study also showed that the CC chemokine CCL-16 mediates chemotaxis via the H4R in eosinophils (46). Thus, histamine might play a role in the accumulation of DC and other cell types in allergic diseases such as atopic dermatitis or contact dermatitis.…”
Section: Discussionmentioning
confidence: 98%
“…To test this possibility, we first generated stable transfectants of human D3 (L1.2-D3) or vector alone (L1.2-vector) using a murine L1.2 pre-B cell line (26). This cell line has been widely used to express cloned chemotactic receptors for the study of their functions (28) and, fortunately, did not express any dopamine receptors endogenously (data not shown). As shown in confirmed that dopamine-induced calcium mobilization in L1.2-D3 was suppressed by raclopride (an antagonist for D2 and D3), U-99194A (an antagonist for D3), and haloperidol (an antagonist for D2, D3, and D4), but not by SCH23390 (an antagonist for D1 and D5) or clozapine (an antagonist for D4) (1,29).…”
Section: Dopamine Induces Calcium Mobilization and Chemotaxis Via D3mentioning
confidence: 99%
“…This was conducted as described previously (28). In brief, cells were suspended at 10 6 cells/ml in HBSS containing 1 mg/ml BSA and 10 mM HEPES (pH 7.4), and loaded with 3 M Fura 2-AM fluorescence dye (Molecular Probes).…”
Section: Calcium Mobilization Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, human eosinophils have recently been shown not to express the histamine H 3 receptor. [48] Thus, histamine-induced human eosinophil apoptosis in the presence of IL-5 is unlikely to be mediated through the histamine H 3 receptor subtype.…”
Section: Discussionmentioning
confidence: 98%